Understanding the Complexity of the Tumor Microenvironment in K-ras Mutant Lung Cancer: Finding an Alternative Path to Prevention and Treatment - Deng, Shanshan; Clowers, Michael J.; Velasco, Walter V.; Ramos-Castaneda, Marco; Moghaddam, Seyed Javad (Frontiers in Oncology, 2020)
Kirsten rat sarcoma viral oncogene (K-ras) is a well-documented, frequently mutated gene in lung cancer. Since K-ras regulates numerous signaling pathways related to cell survival and proliferation, mutations in this gene are powerful drivers of tumorigenesis and confer prodigious survival advantages to developing tumors. These malignant cells dramatically alter their local tissue environment and in the process recruit a powerful ally: inflammation. Inflammation in the context of the tumor microenvironment can be described as either antitumor or protumor (i.e., aiding or restricting tumor progression respectively). Many current treatments, like immune checkpoint blockade, seek to augment antitumor inflammation by alleviating inhibitory signaling in cytotoxic T cells; however, a burgeoning area of research is now focusing on ways to modulate and mitigate protumor inflammation. Here, we summarize the interplay of tumor-promoting inflammation and K-ras mutant lung cancer pathogenesis by exploring the cytokines, signaling pathways, and immune cells that mediate this process.